2015
DOI: 10.1002/wcms.1220
|View full text |Cite
|
Sign up to set email alerts
|

GENESIS: a hybrid‐parallel and multi‐scale molecular dynamics simulator with enhanced sampling algorithms for biomolecular and cellular simulations

Abstract: GENESIS (Generalized-Ensemble Simulation System) is a new software package for molecular dynamics (MD) simulations of macromolecules. It has two MD simulators, called ATDYN and SPDYN. ATDYN is parallelized based on an atomic decomposition algorithm for the simulations of all-atom force-field models as well as coarse-grained Go-like models. SPDYN is highly parallelized based on a domain decomposition scheme, allowing large-scale MD simulations on supercomputers. Hybrid schemes combining OpenMP and MPI are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
223
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 210 publications
(223 citation statements)
references
References 104 publications
(183 reference statements)
0
223
0
Order By: Relevance
“…For MG h , we performed 20 ns MD simulation with the first 5 ns considered as equilibration. MG m1 and MG h trajectories were obtained with GENESIS (Jung et al, 2015) on the K computer. MG m2 was run as a control using NAMD 2.9 (Phillips et al, 2005).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…For MG h , we performed 20 ns MD simulation with the first 5 ns considered as equilibration. MG m1 and MG h trajectories were obtained with GENESIS (Jung et al, 2015) on the K computer. MG m2 was run as a control using NAMD 2.9 (Phillips et al, 2005).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The γ-REMD method induced reorientation of WALP23 due to protein–lipid interactions, resulting in more accurate free energy profile than in NPT MD simulations. They further performed γT-REMD, γ-REMD, and T-REMD simulations of mixed POPC/DMPC lipids, whose results are described below in detail in terms of the effect of surface tension on membrane structures [87]. …”
Section: Enhanced Conformational Sampling Methodsmentioning
confidence: 99%
“…Mori et al simulated mixed POPC/DMPC bilayers by using γT-REMD, T-REMD, γ-REMD, and MD simulations, and examined the effect of the surface tension on the membrane structures with multiple components [87]. In their simulations, they observed that some replicas in γT-REMD showed accelerated mixing of two lipids compared to MD (Fig.…”
Section: Recent Membrane and Membrane Protein Simulations Using Enmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted before, this is a consequence of the relatively high cost of the GBMV implicit solvent model that is used here. 81 Explicit solvent simulations further benefit from better parallelization schemes 82, 83 and GPU acceleration 8486 . However, GPU acceleration is also possible for GB models 87 and the replacement of the very expensive GBMV model by better-performing alternative GB implementations and other implicit solvent models, especially when combined with PRIMO or the PRIMO part of an AA/CG model remains a promising avenue for increased computational efficiency.…”
Section: Resultsmentioning
confidence: 99%